2012
DOI: 10.2298/fil1205065m
|View full text |Cite
|
Sign up to set email alerts
|

On V-r-invexity and vector variational-like inequalities

Abstract: In this paper, we consider the multiobjective optimization problems involving the differentiable V-r-invex vector valued functions. Under the assumption of V-r-invexity, we use the Stampacchia type vector variational-like inequalities as tool to solve the vector optimization problems. We establish equivalence among the vector critical points, the weak efficient solutions and the solutions of the Stampacchia type weak vector variational-like inequality problems using Gordan?s separation theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Vivek Laha laha.vivek333@gmail.com [5][6][7][8], the nonsmooth case [9][10][11][12] and the recent results [13][14][15] for motivations and references.…”
Section: Introductionmentioning
confidence: 99%
“…Vivek Laha laha.vivek333@gmail.com [5][6][7][8], the nonsmooth case [9][10][11][12] and the recent results [13][14][15] for motivations and references.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION Free radical polymerization is one of the most widely employed polymerization techniques which have been successfully applied in the preparation of paints, high molecular weight poly(methyl methacrylate) for safety glass (Plexiglas V R ), and foamed poly (styrene). 1 The conventional approaches for initiating radical polymerization reactions involve thermal decomposition of azo-compounds (e.g., dialkyldiazenes, AIBN), peroxides (e.g., diaroyl peroxides), organometallic compounds (e.g., trialkyltin hydride) etc. However, requirement of higher reaction temperatures is one of the main obstacles associated with these processes.…”
mentioning
confidence: 99%
“…19,20 RAFT reagents such as thiocarbonylthio compounds are commonly used. 3,21,22 In the study reported here, RAFT miniemulsion polymerization of styrene (ST) using dibenzyl trithiocarbonate (DBTTC) 23 -25 as RAFT reagent was investigated. Furthermore, the extremely hydrophobic DBTTC was used as costabilizer in this colloidal system and, thus, no additional costabilizer was needed in retarding Ostwald ripening.…”
Section: Introductionmentioning
confidence: 99%